2005
DOI: 10.1074/jbc.m505277200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Joint Dependence of Pol X Family Polymerase Action in Nonhomologous End Joining

Abstract: DNA double strand breaks (DSBs) can be rejoined directly by the nonhomologous end-joining (NHEJ) pathway of repair. Nucleases and polymerases are required to promote accurate NHEJ when the terminal bases of the DSB are damaged. The same enzymes also participate in imprecise rejoining and joining of incompatible ends, important mutagenic events. Previous work has shown that the Pol X family polymerase Pol4 is required for some but not all NHEJ events that require gap filling in Saccharomyces cerevisiae. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 43 publications
3
114
1
Order By: Relevance
“…The possible use of these enzymes during NHEJ seems to be due to their capacity to synthesize DNA from less stable primer structures compared to replicative polymerases, such as primers that encompass a DNA template with a gap 19 (Fig.3c). Lieber and colleagues, using purified polymerase proteins in vitro, showed that a competitive hierarchy exists in the recruitment of polymerases to the DNA during NHEJ, with Polµ being preferentially recruited over Polλ in the absence of TdT, whereas the reverse was true when TdT was present 12 .…”
Section: V(d)j Recombination and Dna Polymerasesmentioning
confidence: 99%
“…The possible use of these enzymes during NHEJ seems to be due to their capacity to synthesize DNA from less stable primer structures compared to replicative polymerases, such as primers that encompass a DNA template with a gap 19 (Fig.3c). Lieber and colleagues, using purified polymerase proteins in vitro, showed that a competitive hierarchy exists in the recruitment of polymerases to the DNA during NHEJ, with Polµ being preferentially recruited over Polλ in the absence of TdT, whereas the reverse was true when TdT was present 12 .…”
Section: V(d)j Recombination and Dna Polymerasesmentioning
confidence: 99%
“…Pol4, the only Pol X polymerase in S. cerevisiae, is dispensable for simple religation NHEJ [9], but is strictly required when a gap in the joint must be filled using an unstable primertemplate pair, as is the case with 3' overhangs [10]. Other polymerases can compensate for the loss of Pol4 when a stably paired primer is available, for example at 5' overhangs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other polymerases can compensate for the loss of Pol4 when a stably paired primer is available, for example at 5' overhangs [10]. However, Pol4 is surprisingly not required for joining of nicked 3' overhang DSBs with 5' hydroxyls [10], even though yeast lack a 5' kinase and thus demand resynthesis of the damaged 5' nucleotide [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pol b, consequently, does not stably associate with NHEJ core factors at ends, nor does it effectively promote NHEJ in many contexts in vitro [Mahajan et al, 2002;Ma et al, 2004;Nick McElhinny et al, 2005]. Nevertheless, Pol b is able to partly compensate for Pol4 deficiency during NHEJ when overexpressed in yeast [Daley et al, 2005] and Pol b-deficient mouse embryonic fibroblasts (MEFs) are moderately sensitive to ionizing radiation [Horton et al, 2008]. Unlike other vertebrate Pol X members, Pol b deficiency results in embryonic lethality in mice [Gu et al, 1994;Bertocci et al, 2006].…”
Section: Pol Bmentioning
confidence: 99%
“…This is apparent from the analysis of repair events from cells that survive (and thus inaccurately repair) chromosome breaks generated after constitutive induction of the HO endonuclease [Wilson and Lieber, 1999;Li et al, 2012]. More systematic analysis of substrate specificity [Daley et al, 2005;Daley and Wilson, 2008] indicates S. cerevisiae Pol4 is essential for synthesis required after alignment of 3 0 overhangs leaves behind gaps in both strands. By comparison, synthesis in many other contexts (e.g., after alignment leaves a gap in only one strand, or after alignment of 5 0 overhangs) is independent of Pol4, indicating that other polymerases are sufficient for these substrates.…”
Section: Pol4mentioning
confidence: 99%